Preparing to manage injury burden of Bihar - Verma, Vikas; Singh, Chandra Mani; Singh, Girish Kumar; Kumar, Santosh; Kumar, Anil; Dhungana, Hom Nath (Indian Journal of Community Health, 2015)
Introduction: Trauma care in Bihar is beset by a number of problems namely lack of funds, one of the highest population densities in the country, far flung flood prone areas that remain inaccessible to healthcare for several months of an year, lack of formal pre-hospital care services and an organized system of trauma care.. EMS services are run by many different organizations such as government, police, fire, hospital or private organizations. There is lack of coordination between these organizations. First response to the injured is very often provided by the police who tend to transfer the patient to the nearest government health care centre. There is no linkage with hospital trauma services. This paper presents the interim results of a plan developed and being implemented at AIIMS, Patna in collaboration with the government of Bihar and Adams Cowley shock trauma trauma centre, Baltimore, USA. Methods: Participants from the Bihar police and Bihar health services were nominated by the government of Bihar. One hundred fifty one participants were imparted a 3 day training that included basics for managing airway, breathing, circulation, extrication, fractures, and spine injuries. Incident managment, approach to mass casualty and safe transport were also part of the cirriculum. All participants were required to take a pre-test before the training, a post test at the end of the training and another post test after 6 months after the training. Whether participants attended to emergencies before and after the training was also soought. Paired t tests were used to compare the means of tests. Independent t test was used to compare difference of means in the groups that attended to emergencies in the six months after the training with those that did not attend to emergencies during the 6 months after the training. Results:One hundred fifty one participants were trained. Of the 151 participants 55 (36.4%) belonged to Bihar police and 96 (73.6%) belonged to Bihar health services. The average number of emergencies attended by the participants was 8.6 per month. However, 48 participants had not attended to an emergency during the last six months. Mean post-test score 1 was significantly higher than mean pre-test score. Mean post-test score 2 was significantly higher than mean pre-test score. Mean post-test 1 was significantly higher than mean post-test score 2. Mean post-test 1 score was found to be significantly higher (p value 0.00) in those that attended to emergencies in the 6 months after training than those that did not attend to emergencies in the 6 months after training. Difference of means (Post-test 1 Vs Post-test 2) in the two groups was significantly lower in the group that attended to emergencies in six months after training. Discussion: 48 participants had not attended to emergencies prior to training. Of these 48 participnats, 47 did not attend to any emrgency in the 6 months after the training, This probably reflects poor selection of participants and lack of cooridanation between various department of the Bihar goverment. Our finding that our module was able to increase the knowledge is similar to other studies that have reported enhanced knowledge as a result of training. Increase in knowledge levels was sustained for a period of six months. Attending to emergencies in 6 months after the training helped in retention of the knowledge. Conclusion: The plan developed and being implemented at AIIMS, Patna in collaboration with the government of Bihar and Adams Cowley shock trauma trauma centre, Baltimore, USA is successful in raising knowledge levels which are sustained for a period of six months. A system for identifying participants needs to be developed so that those who regularly attend to emergencies are preferred to those that do not attend to emergencies regularly. Also those who have undergone the training should be utilized in roles that require attending to emergencies.